TIME DOMAIN FINITE DIFFERENCE NUMERICAL METHOD OF ANALYSIS OF DIRECT LIGHTNING ELECTROMAGNETIC PULSE AT GROUND HORIZONTAL WIRE - Pejtamalli, Xhemali; Cipo, Piro (European Scientific Journal, ESJ, 2015)
Nowadays ,there are many different studies to analyze the transient process for the spread of the lightning electromagnetic pulse in transmission line with distributed parameters. According to the researcher’s interests, works are focused into different directions. This paper presents a model of analysis of the weaning process of spreading the lightning electromagnetic pulse at ground wire located horizontally with the numerical method of finite differences in time zone. Through this study, we can estimate the values of the step voltage, touch voltage, electromagnetic compatibility problems and the over voltage analysis. The mathematical model of ground wire is described by differential equations with partial derivatives of hyperbolic type, whose solution is made with the numerical method of finite differences. Discretiding in space and time is accomplished with the Lax-Wendroff method.